On the genesis of thought and language : on the emergence of concepts and propositions, the nature and structure of human categories, on the impact of culture on thought and language - Koshelev, A. D. (Alekseĭ Dmitrievich) (LRC Publishing House ; Academic Studies Press, 2020)
In On the Genesis of Thought and Language, linguist Alexey Koshelev explores fundamental questions of how human concepts arise in a child, why concepts appear in a child before words, the genesis of language, and why there are so many languages.